Interface shear strength between geotextile and soil-sodium bentonite liner / Nur Aisyah Kasim - Kasim, Nur Aisyah (2019)
Landfill liner system is designed to provide maximum protection to the environment. Installation of the liner system is supervised and inspected to ensure that it meets or exceeds environmental standards. The installation of geotextile on landfill is spread by layers and will be overlapping between each layer about 0.5 m to 1.0 m. However, the occurrence of the soil movements is always expected to occur.